Attuning to the World: The Diachronic Constitution of the Extended Conscious Mind - Kirchhoff, Michael D.; Kiverstein, Julian (Frontiers in Psychology, 2020)
It is a near consensus among materialist philosophers of mind that consciousness must somehow be constituted by internal neural processes, even if we remain unsure quite how this works in the brain. Even friends of the extended mind theory have argued that when it comes to the material realisers of conscious experience, the boundary of skin and skull will prove to be somehow privileged. They have argued that only processes taking place within the skin and skull boundary can serve as the material substrate of conscious experience. Such arguments have however typically conceived of the constitution of consciousness in synchronic terms, making a firm separation between proximate mechanisms, and their ultimate causes. We argue that to properly explain the processes involved in the constitution of some experiences ultimate causes need to be embedded within proximate explanation. We focus on the case of what we call phenomenal attunement in this paper. The phenomenon we have in mind is most evident in cases in which it is missing such as when one travels to a foreign land for the first time. The feeling of being at home in the world is a ubiquitous and taken for granted structure of our conscious experience of the world. It is this structure of experience we will name phenomenal attunement. We use the notion of diachronic constitution to argue that phenomenal attunement is extended. Phenomenal attunement we will argue is constituted by cycles of embodied and world-involving engagement whose dynamics are constrained by cultural practices. Thus it follows that an essential structure of the conscious mind, the absence of which profoundly transforms conscious experience, is extended.